Shared Decision Making for Radioiodine Therapy and the Actual Pattern of Care in Intermediate-Risk Differentiated Thyroid Carcinoma - Eilsberger, Friederike; Luster, Markus; Reiners, Christoph (Frontiers in Nuclear Medicine, 2022)
Radioiodine therapy (RAI) is usually a standard procedure performed after thyroidectomy in differentiated thyroid cancer (DTC). While the indication for RAI in high-risk patients has been established in various national and international guidelines, there is an ongoing discussion with regard to intermediate-risk patients. In addition to the inconsistent definition of this risk category, the absence of large multinational prospective randomized controlled trials forms the basis of the debate. In this context, the actual pattern of care and national guidelines in the country where the patient is living plays an important role with respect to regional iodine supply and goiter prevalence, preoperative diagnostics (fine needle aspiration biopsy), and corresponding surgical strategies. Participatory decision-making between physician and informed patient, which is demanded in principle today anyway, is of particular importance in this situation. This article will discuss the approach of shared decision making for radioiodine therapy in intermediate-risk DTC.